Critical success factors evaluation of e-CRM in local industry / Salina Mokhtar - Mokhtar, Salina (2005)
E-CRM has become the latest paradigm in the world of CRM. E-CRM has becoming more necessary as business strategy with intent to provide better customer service and satisfaction due to the lower cost but increase the revenues. Therefore, the key area performance or known as the critical success factors need to be determined to ensure the success of E-CRM. This research has examined and analyst the critical success factors of E-CRM based on the existing theoretical framework. The factors are operational perceived benefits, strategic perceived benefits, top management support, technology readiness and finally knowledge management capabilities. Besides that, this research also identifies the goals of E-CRM and compares the benefits from E-CRM implementation. This research has been conducted in local industry in Klang Valley area which are involving twelve companies to participate in this research. There are 100 questionnaire have been distributed among the respondents in such organization. The data analysis is performed using ANOVA comparison.